EKOLOGI VERTICILLIUM TRICORPUS DI PERKEBUNAN KAKAO KABUPATEN MADIUN - , Roosmarrani Setiawati, Prof. Dr. Ir. Bambang Hadisutrisno, DAA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Verticillium tricorpus, one of fungi from genus Verticillium, is potential to be developed and used as a biological control, particularly to controlling pest that drills the fruit of cacao (Hama PBK) caused by Conopomorpha cramerella. This research in turn aims to find out the survival of V. tricorpus in cacao plant and the environmental effect on the growth of this fungus in field. This research is conducted both in laboratory and in field. In laboratory, the environmental factors analyzed in this research include 5 degrees of temperature, those are 15, 20, 25, 30, and 35 Â°C, and 4 degrees of light intensity, namely 0 lux (dark condition), 1000, 2000, and 3000 lux. The research in field meanwhile is to find out the development and the establishment of V. tricorpus by relating it to temperature, humidity relative to the air, and the wind velocity. The result of the research shows that the vegetative growth and conidial development of V. tricorpus in PDA medium can reach the optimum at 25 Â°C and in a fully dark condition (0 lux). The spread of conidium of V. tricorpus in field occurs at night in temperature between 20â30 Â°C, humidity relative that reaches 70â80 %, and the wind velocity ranging 0.5â1,0 km/hour. The application of V. tricorpus on cacao could decrease the intensity of PBK pest attack until 46.67 %.